Evaluation of selection criteria in laying quail (Coturnix coturnix japonica) - Stivanin, T. E.; Costa Maia, F. M.; Migliorini, E.; Kluska, S. [UNESP]; Amorim, S. T. [UNESP]; Lovatto, F. S.; Martins, E. N. (My University, 2019)
The primary aim of the commercial exploration of quail in Brazil is to increase egg production. The characteristics of the genetic groups used are not well known, making it difficult to increase eggs production. The objective of this study is to evaluate selection criteria to increase the number of eggs produced in two lineage of laying quail. In this sense, genetic parameters were estimated and calculated the indirect and direct responses to selection. The genetic gain was calculated based on the selection of partial production in the complete egg production. The indirect response showed to be more efficient in terms of genetic gain compared to the direct selection, indicating that the use of the first 60 days is the ideal period for selection of quail, providing satisfactory gain in egg production compared to the total production period. The use of this period allowed the early identification of superior individuals, increased the total egg production and the genetic gain, reducing the generation interval and making it possible to carry outtwo selections per year.
Keywords: Egg production; Genetic gain; Genetic parameters; Selection efficiency